Comparative gyrokinetic analysis of JET baseline H-mode core plasmas with carbon wall and ITER-like wall. (22nd February 2016) - Tegnered, D; Strand, P; Nordman, H; Giroud, C; Kim, Hyun-Tae; Maddison, G P; Romanelli, M; Szepesi, G
Abstract: Following the change of plasma facing components at JET from a carbon wall (CW) to a metal ITER-like wall (ILW) a deterioration of global confinement has been observed for H-mode baseline experiments. The deterioration has been correlated with a degradation of pedestal confinement with lower electron temperatures at the top of the edge barrier region. In order to investigate the change in core confinement, heat transport due to Ion Temperature Gradient (ITG)/Trapped Electron Mode (TEM) turbulence is investigated using the gyrokinetic code GENE. Two pairs of CW and ILW discharges that are matched according to several global parameters are simulated at mid radius. The simulations included effects of collisions, finite β, realistic geometries, and impurities. A sensitivity study is performed with respect to the key dimensionless parameters in the matched pairs. The combined effect of the relative change in these parameters is that the ITG mode is destabilized in the ILW discharges compared to the CW discharges. This is also reflected in nonlinear simulations where the ILW discharges show higher normalized ion and electron heat fluxes and larger stiffness. The ion energy confinement time within is found to be comparable while the electron confinement time is shorter for the ILW discharges. The core confinement in the ILW discharges is expected to improve if the edge pedestal is recovered since that would favourably change the key plasma parameters that now serve to destabilize them.